MBD4 guards against methylation damage and germ line deficiency predisposes to clonal hematopoiesis and early-onset AML - Sanders, Mathijs A.; Fröhling, Stefan (Blood, 2018)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - The tendency of 5-methylcytosine (5mC) to undergo spontaneous deamination has had a major role in shaping the human genome, and this methylation damage remains the primary source of somatic mutations that accumulate with age. How 5mC deamination contributes to cancer risk in different tissues remains unclear. Genomic profiling of 3 early-onset acute myeloid leukemias (AMLs) identified germ line loss of MBD4 as an initiator of 5mC-dependent hypermutation. MBD4-deficient AMLs display a 33-fold higher mutation burden than AML generally, with >95% being C>T in the context of a CG dinucleotide. This distinctive signature was also observed in sporadic cancers that acquired biallelic mutations in MBD4 and in Mbd4 knockout mice. Sequential sampling of germ line cases demonstrated repeated expansion of blood cell progenitors with pathogenic mutations in DNMT3A, a key driver gene for both clonal hematopoiesis and AML. Our findings reveal genetic and epigenetic factors that shape the mutagenic influence of 5mC. Within blood cells, this links methylation damage to the driver landscape of clonal hematopoiesis and reveals a conserved path to leukemia. Germ line MBD4 deficiency enhances cancer susceptibility and predisposes to AML.
Gesehen am 16.05.2019